Manajemen Madrasah Berbasis Karakter - Adnan, Adnan (SYAMIL: Jurnal Pendidikan Agama Islam (Journal of Islamic Education), 2017)
Madrasah as one educational institution has a role in implementing character-based education. In order for the education to be carried out later to meet the expectations that have been proclaimed, it must be formulated early on how management or management should be done. For that reason, in this paper will be discussed specifically about the management of madrasah in organizing character-based education. Character-based madrasah management is the management of madrasah that always prioritizes the principles of fairness, integrity, honesty, dignity, service, quality, and growth in every component of its management.